Hydrogeological modeling in groundwater engineering structures - Bonomi, Tullia; Brambilla, Arianna; Gasparetti, Davide; Modenesi, Alessandro (Italian journal of engineering geology and environment, 2008)
The aim of this study is to create an equalization and homogenization tank in an area adjacent to the depuration plant of Verziano (Brescia Province, Italy), using existing unconfined groundwater. This has caused problems in both planning and implementation of this project and has also affected costs. A flow model was elaborated by means of MODFLOW software in the steady-state mode, which considered the various interventions to be undertaken in order to lower the water table (bulkheads, wellpoints and drains) and create the underground tank. The modeled area is 18,492 m2 and was discretized with a dishomogeneous grid consisting of 96 lines and 247 columns. The vertical dimension was sub-divided into 44 layers.A number of simulations were elaborated in an attempt to recreate the real sequence of the interventions undertaken and some significant elements have been. From the simulation results using bulkheads, it was shown that the construction of diaphragms allows the flow of groundwater to be diverted under the panels, according to grain-size distribution. From the wellpoint simulations it was shown that when two microwells are placed too close together, the system becomes inefficient as there is interference between the two cones. The interventions considered cause a variation of groundwater localized only in the area of the tank, without exerting any influence on hydrogeologic features (springs) present in the surrounding area.